2000
DOI: 10.1038/76889
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a receptor for BLyS demonstrates a crucial role in humoral immunity

Abstract: B lymphocyte stimulator (BLyS) is a member of the tumor necrosis factor (TNF) superfamily. BLyS stimulates proliferation of, and immunoglobulin production by, B cells. However, the relative importance of BLyS in physiological B cell activation is unclear. We identified a B cell receptor for BLyS through expression cloning as TACI, an orphan TNF receptor homologue of unknown function. Binding of BLyS to TACI activated signaling by nuclear factor-kappa B (NF-kappa B). In vitro soluble TACI-Fc fusion protein bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
141
1
3

Year Published

2001
2001
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(150 citation statements)
references
References 41 publications
5
141
1
3
Order By: Relevance
“…4, right panel). These data are consistent with previously published reports using BAFF inhibitors (19,22).…”
Section: Baff Blockade Inhibits T-dependent Ab Responses Including Hsupporting
confidence: 83%
See 2 more Smart Citations
“…4, right panel). These data are consistent with previously published reports using BAFF inhibitors (19,22).…”
Section: Baff Blockade Inhibits T-dependent Ab Responses Including Hsupporting
confidence: 83%
“…A single study using the BAFF receptor decoy, transmembrane activator and calcium-modulator and cyclophilin ligand interactor (TACI)-Fc, reported a complete absence of GCs in treated mice (19). However, this same report also noted the presence of high-affinity anti-(4-hydroxy-3-nitrophenyl)acetyl (NP) Ab, albeit at low levels.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Among these factors, BAFF has a relatively well-defined role in the survival of immature and naĂŻve B cells and in promoting Ab responses [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…It is now believed that sTALL-1 promotes either differentiation of B cells or survival of mature B cells (25)(26)(27)(28). Administration of recombinant sTALL-1 or overexpression of sTALL-1 in mice leads to increased numbers of mature B lymphocytes, splenomegaly, anti-DNA Abs, proteinuria, and glomerulonephritis, phenotypes that mimic those of systemic lupus erythemia (3,5,14,29,30). Conversely, it has been shown that recombinant soluble TACI-Ig fusion proteins can significantly inhibit progression of lupus-like autoimmune syndrome and collagen-induced arthritis in animal models (27,31).…”
Section: Tnfr-associatedmentioning
confidence: 99%